Heterogeneous Firms and International Trade: The Role of Productivity and Financial Fragility - Tiziana Assenza; Domenico Delli Gatti; Jakob Grazzini; Giorgio Ricchiuti (Center for Economic Studies and ifo Institute (CESifo), 2016)
Starting from the premise that productivity is heterogeneous across firms, Melitz (2003) explains why individual productivity is key in determining the capability of a firm to export. In this paper we build a model along Melitz's lines to show that also financial capacity, captured by the level of individual net worth, affects the behaviour of firms on international markets. We show that firms with low productivity may still be able to penetrate foreign markets provided they have enough net worth to incur the cost of exporting. In this setting, we explore the effects of changes in transport costs, fixed costs for exporters and of financial constraints.
Keywords: E44; F12; F14; F21; 330; productivity; net worth; international trade; heterogeneous firms